Developmental regulation of neuronal gene expression by Elongator complex protein 1 dosage. (July 2022) - Morini, Elisabetta; Gao, Dadi; Logan, Emily M.; Salani, Monica; Krauson, Aram J.; Chekuri, Anil; Chen, Yei-Tsung; Ragavendran, Ashok; Chakravarty, Probir; Erdin, Serkan; Stortchevoi, Alexei; Svejstrup, Jesper Q.; et al.
Abstract: Familial dysautonomia (FD), a hereditary sensory and autonomic neuropathy, is caused by a mutation in the Elongator complex protein 1 ( ELP1 ) gene that leads to a tissue-specific reduction of ELP1 protein. Our work to generate a phenotypic mouse model for FD headed to the discovery that homozygous deletion of the mouse Elp1 gene leads to embryonic lethality prior to mid-gestation. Given that FD is caused by a reduction, not loss, of ELP1, we generated two new mouse models by introducing different copy numbers of the human FD ELP1 transgene into the Elp1 knockout mouse ( Elp1 −/− ) and observed that human ELP1 expression rescues embryonic development in a dose-dependent manner. We then conducted a comprehensive transcriptome analysis in mouse embryos to identify genes and pathways whose expression correlates with the amount of ELP1 . We found that ELP1 is essential for the expression of genes responsible for nervous system development. Further, gene length analysis of the differentially expressed genes showed that the loss of Elp1 mainly impacts the expression of long genes and that by gradually restoring Elongator, their expression is progressively rescued. Finally, through evaluation of co-expression modules, we identified gene sets with unique expression patterns that depended on ELP1 expression.